Prediction of major adverse cardiac events of patients with acute coronary syndrome by using TIMI risk index - Ehsan, Mohammad Abul; Mahmood, Md Manzoor; Khan, Laila Farzana; Salim, Md Abu (Journal of Dhaka National Medical College & Hospital, 2013)
Patient with acute coronary syndrome (ACS) has considerable variability in outcome and mortality risk. The Thrombolysis in Myocardial Infarction (TIMI) risk index (TRI) for unstable angina/non ST elevation myocardial infarction & ST elevation myocardial infarction were a convenient bedside clinical risk score for predicting 30 days mortality at presentation with ACS. This study was done to predict and validate major adverse cardiac events in patients of ACS thus it will help us to quantify risk, observe the prognostic value and to guide appropriate therapy by using TRI. This prospective study was carried out in the department of cardiology, BSMMU, Dhaka from April, 2011 to March, 2012. After considering all ethical issues, data were collected from 279 patients attending at cardiac emergency department with the presentation of ACS. History & physical examinations were done. TIMI risk index were calculated for each patient. The major adverse cardiac events (recurrent myocardial infarction, urgent revascularization, and all-cause mortality) were measured for next 30 days in hospital setting & outpatient department by follow up. After follow-up, Cox univariate and multivariate regression analysis were used to evaluate the influence of potential risk factors on duration of event-free survival, and likelihood ratio tests to assess the outcome. Major adverse events of TIMI risk index group 1, 2, 3, 4 & 5 were 0%, 0%, 3.7%, 12.9% & 19.2% respectively in UA/NSTEMI group. In STEMI group major adverse cardiac events of TIMI risk index group 1, 2, 3, 4 & 5 were 0%, 4.7%, 12.5%, 17.1% & 24.1% respectively. Increasing TRI were associated with increased risk of major adverse cardiac events. These score were a valid tool for risk assessment. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16024 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 52-57